2016
DOI: 10.2503/hortj.mi-085
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Functional Analysis of Two Gibberellin 20-Oxidase Genes from Satsuma Mandarin (<i>Citrus unshiu</i> Marc.)

Abstract: Satsuma mandarin (Citrus unshiu Marc.) has two GA 20-oxidase genes, CuGA20ox1 and CuGA20ox2, and the genomic sequence for CuGA20ox1 is shorter than that for CuGA20ox2, although the coding region of cDNA for CuGA20ox1 is slightly longer than that for CuGA20ox2. Southern blot analysis revealed that 12 Citrus cultivars examined and trifoliate orange [Poncirus trifoliata (L.) Raf.] have at least two types of GA 20-oxidase genes, such as CuGA20ox1 and CuGA20ox2 genes. CuGA20ox1 and CuGA20ox2 were differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A previous study identified two GA 20-oxidase genes from Satsuma mandarin and confirmed their function using transgenic Arabidopsis. Consistent with the accumulation of active GAs in the ovaries at around anthesis, CuGA20ox2 was specifically expressed in the flower bud just before anthesis in Satsuma mandarin (Kotoda et al, 2016). In this study, Satsuma mandarin GA 2oxidase genes encoding enzymes with an inactivation activity of GAs were characterized because the accumulation of active GAs is regulated by the balance between their synthesis and inactivation.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…A previous study identified two GA 20-oxidase genes from Satsuma mandarin and confirmed their function using transgenic Arabidopsis. Consistent with the accumulation of active GAs in the ovaries at around anthesis, CuGA20ox2 was specifically expressed in the flower bud just before anthesis in Satsuma mandarin (Kotoda et al, 2016). In this study, Satsuma mandarin GA 2oxidase genes encoding enzymes with an inactivation activity of GAs were characterized because the accumulation of active GAs is regulated by the balance between their synthesis and inactivation.…”
Section: Introductionmentioning
confidence: 52%
“…The expression pattern of CuGA2ox4 resembled that of CuGA20ox1 in the reproductive tissues of the adult trees in that both genes were expressed in juice sacs in November and December and in peel in December (Fig. 3A; Kotoda et al, 2016), suggesting that CuGA2ox4 and CuGA20ox1 act in concert to regulate the accumulation of active GAs in fruit at the maturing stage. Because these genes are expressed in both juice sacs and peel, they might be involved in the occurrence of peel puffins to some extent.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, Kishu shows no parthenocarpy (Shimizu, T., unpublished) but Satsuma is an exceptionally high and stable parthenocarpic variety [117]. Kotoda et al isolated two gibberellin 20-oxidase genes from Satsuma thought to be involved in parthenocarpy, and demonstrated their different biological functions [71]. Very recently, Kotoda et al isolated three gibberellin 2-oxidase genes of Satsuma involved in the degradation of bioactive gibberellic acid [132].…”
Section: Discussionmentioning
confidence: 99%
“…Citrus genome sequence resources in public databases, including BAC end sequences of Clementine [69] and Satsuma [70,71], and whole genome shotgun sequences of sweet orange ‘Ridge Pineapple’ in the trace file repository of Sanger reads (ftp://ftp.ncbi.nlm.nih.gov/pub/TraceDB/citrus_sinensis/), were also used for DNA marker design. Preliminary evaluation of the quality and length of each of these data sets was carried out using pregap4 [72], then a consensus sequence set was obtained for each set with Mira assembler [73] to reduce redundancy.…”
Section: Methodsmentioning
confidence: 99%